Transplanted terminally differentiated induced pluripotent stem cells are accepted by immune mechanisms similar to self-tolerance - de Almeida, Patricia .E; Meyer, Everett H.; Kooreman, Nigel G.; Diecke, Sebastian; Dey, Devaveena; Sanchez-Freire, Veronica; Hu, Shijun; Ebert, Antje; Odegaard, Justin; Mordwinkin, Nicholas M.; Brouwer, Thomas P.; Lo, David; et al. (Nature communications, 2014)
The exact nature of the immune response elicited by autologous-induced pluripotent stem cell (iPSC) progeny is still not well understood. Here we show in murine models that autologous iPSC-derived endothelial cells (iECs) elicit an immune response that resembles the one against a comparable somatic cell, the aortic endothelial cell (AEC). These cells exhibit long-term survival in vivo and prompt a tolerogenic immune response characterized by elevated IL-10 expression. In contrast, undifferentiated iPSCs elicit a very different immune response with high lymphocytic infiltration and elevated IFN-γ, granzyme-B and perforin intragraft. Furthermore, the clonal structure of infiltrating T cells from iEC grafts is statistically indistinguishable from that of AECs, but is different from that of undifferentiated iPSC grafts. Taken together, our results indicate that the differentiation of iPSCs results in a loss of immunogenicity and leads to the induction of tolerance, despite expected antigen expression differences between iPSC-derived versus original somatic cells. Transplantation of mouse-induced pluripotent stem cells (iPSCs), but not of iPSC-derived terminally differentiated cells, triggers a T-cell-dependent immune response. Here the authors show that iPSC-derived endothelial cells are accepted by self-tolerance mechanisms similar to autologous endothelial cells.